Ash vs evil dead. The complete first season [videorecording (DVD)] - Campbell, Bruce, 1958-; Lawless, Lucy, 1968-; Jones, Jill Marie, 1975- (Anchor Bay Entertainment, 2016)
Ash is the stock boy, who is an aging lothario and chainsaw-handed monster hunter who has spent the last 30 years avoiding responsibility, maturity and the terrors of the Evil Dead. When a Deadite plague threatens to destroy all of mankind, Ash is finally forced to face his demons; personal and literal. Destiny, it turns out, has no plans to release the unlikely hero from its "Evil" grip.